Studi Monitoring Kualitas Air pada Tambak Intensif Budidaya Udang Vaname, Situbondo - Diana Putri Renitasari; Yunarty Yunarty; Siti Asma (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The purpose of this study was to monitor water quality in white leg shrimp ponds. The study method used was descriptive with quantitative descriptive analysis. The descriptive method was carried out by taking samples and direct observation at the research site. The results observations of salinity in the ponds of pond 3, pond 4, and pond 5 decreased during the maintenance period because there was an addition of fresh water in the ponds. Monitoring of TOM, alkalinity and pH levels during the maintenance period in the pond were still at optimum levels for the growth of white leg shrimp. Measurements of green and yellow vibrio bacteria ranged from 102 until 103. The plankton types were Nannochloropsis sp, Tetraselmis sp, Chlorella sp, Chetocero sp., Coscinodiscus sp, Oscilatoria sp, and Isochrysis most commonly found in ponds. These plankton was among those that shrimp-like.